2009
DOI: 10.1155/2009/187015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of FR‐91 on Immune Cells from Healthy Individuals and from Patients with Non‐Hodgkin Lymphoma

Abstract: The immune system is subject to destruction and dysfunction as a result of attacks by pathogenic and environmental agents. In addition, many clinical situations exist in which it is desirable to stimulate or suppress the immune system. The present study evaluated the screening efficacy of flow cytometric lymphocyte subset typing in peripheral blood mononuclear cells from healthy individuals (HI) and from patients with non-Hodgkin lymphoma (NHL) treated with different concentrations of FR-91, a standardized lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…It has also been shown that the upregulation of Cx43 expression can promote the activation of CD4 + T lymphocytes ( 10 , 16 , 38 ). Given that arterial hypertension activates T lymphocytes ( 1 ), ConA is used as a T cell activator that induces various cytokine secretions ( 39 , 40 ). In addition, to confirm the involvement of GJs in lymphocyte proliferation after activation, lymphocytes were treated with a Cx extracellular loop mimetic peptide (Gap27), which can restrictintercellular communication across GJs and reduce or block Cx hemichannel function in CD4 + T cells and other cell systems (i.e., non-diabetic cells) ( 16 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the upregulation of Cx43 expression can promote the activation of CD4 + T lymphocytes ( 10 , 16 , 38 ). Given that arterial hypertension activates T lymphocytes ( 1 ), ConA is used as a T cell activator that induces various cytokine secretions ( 39 , 40 ). In addition, to confirm the involvement of GJs in lymphocyte proliferation after activation, lymphocytes were treated with a Cx extracellular loop mimetic peptide (Gap27), which can restrictintercellular communication across GJs and reduce or block Cx hemichannel function in CD4 + T cells and other cell systems (i.e., non-diabetic cells) ( 16 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…To detect cytokine inhibition, α-mangostin was combined with ConA to treat PBMCs. ConA is a T-cell activator that subsequently induces various cytokine secretions [11,12]. Ten µg/mL of ConA was not toxic to the cells (> 95% of cell survival) and led to the highest cytokine secretion (data not shown).…”
mentioning
confidence: 93%
“…In the present study, we investigated the effect of FR91, a standardized lysate of microbial cells belonging to the Bacillus genus which has been previously shown to have significant immunomodulatory effects tested on human tumor cell lines [ 12 ], on colonic inflammation induced by 8-week exposure of 2% DSS in the drinking water and, in particular, whether FR91 affects colorectal inflammation. We found that the six-week treatment resulted in a slightly reduction of colorectal lesions at lower dosis (5% FR91) and a moderate-to-complete reduction at higher dosis (10–20% FR91).…”
Section: Discussionmentioning
confidence: 99%